You are on page 1of 3

y 1=a 0+ a1 x 11 +a2 x 12 +a3 x 13

y 2=a 0+ a1 x 21+ a2 x 22+a 3 x 23

y i=a 0+ a1 x i 1+ a2 x i 2+ a3 x i3

y n=a0+ a1 x n 1+ a2 x n 2+ a3 x n 3

( yi , xi 1 , xi 2 , xi 3)

F= ( y i y i)

i=1

F= ( a0 +a1 x i 1+ a2 x i 2+ a3 x i 3 y i )2
i=1

dF
= ( a + a x + a x +a x y i )=0
d (a0 ) i=1 0 1 i1 2 i 2 3 i 3
n

i=1

i=1

i=1

i=1

i=1

i=1

i=1

i=1

i=1

a 0 + a1 x i 1 + a2 x i 2 + a3 x i 3 = y i
a0 n+a1 x i 1 +a2 x i 2 +a3 xi 3= y i
n

dF
= x ( a +a x + a x + a x y )=0
d (a1 ) i=1 i 1 0 1 i 1 2 i 2 3 i 3 i

i=1

i=1

i=1

i=1

i=1

a0 xi 1 +a1 xi 1 x i 1+ a2 x i 2 xi 1 +a 3 x i3 x i 1= y i x i 1
n

dF
= x ( a +a x + a x + a x y ) =0
d (a2 ) i=1 i 2 0 1 i 1 2 i 2 3 i 3 i
n

i=1

i=1

i=1

i=1

i=1

a0 xi 2 +a1 xi 1 x i 2+ a2 x i 2 x i2 +a 3 x i3 xi 2= y i xi 2

dF
= x ( a +a x +a x +a x y ) =0
d (a3 ) i=1 i 3 0 1 i 1 2 i 2 3 i 3 i
n

i=1

i=1

i=1

i=1

i=1

a0 xi 3 +a 1 xi 1 x i 3 +a2 x i 2 x i 3+ a3 x i 3 x i3 = y i x i 3

En resumen
n

i=1

i=1

i=1

i=1

a0 n+a1 x i 1 +a2 x i 2 +a3 xi 3= y i


n

i=1

i=1

i=1

i=1

i=1

i=1

i=1

i=1

i=1

i=1

i=1

i=1

i=1

i=1

i=1

a0 xi 1 +a1 xi 1 x i 1+ a2 x i 2 xi 1 +a 3 x i3 x i 1= y i x i 1

a0 xi 2 +a1 xi 1 x i 2+ a2 x i 2 x i2 +a 3 x i3 xi 2= y i xi 2

a0 xi 3 +a 1 xi 1 x i 3 +a2 x i 2 x i 3+ a3 x i 3 x i3 = y i x i 3

xi 1

i=1

i=1
n

xi 2 xi 3

i=1

i=1

i=1

i=1

i=1
n

i=1
n

i=1
n

x i 1 x i 1 xi 1 xi 2 x i 1
x i 2 x i 1 xi 2 xi 2 x i 2
i=1

i=1

yi
i=1

a
x i 3 x i1 a0
i=1
1=
n
a2
x i 3 x i2 a3
i=1
n

x i 3 x i 1 xi 3 xi 2 x i 3 x i 3 x i3
i=1

)( )
n

i=1

()

yi xi 1
i=1
n

yi xi 2
i=1
n

yi xi 3
i=1